Climate regulation costs and firms’ distress risk - Lambertides, Neophytos; Tsouknidis, Dimitris (My University, 2023)
In 2013, the European Union's Emission Trading Scheme (EU-ETS) entered Phase III. The majority of emission permits in Phase III are auctioned instead of being allocated for free as in Phases I and II. Using a difference-in-differences method, we show that this change has led to an increase in the financial distress risk of the EU-ETS-regulated firms when compared to unregulated firms, suggesting that the EU-ETS imposes a significant financial burden on regulated firms. This result is robust to an array of validation tests, alleviating concerns that it is driven by unobserved factors. In additional analyses we show that the increase in distress risk of regulated firms during Phase III can be explained by, (i) an additional climate regulation cost to purchase pollution permits and (ii) a low average environmental score that possibly (via high sustainability risk) lowers investors expectations regarding firms’ performance. Our findings also show that the distress risk increase is higher for regulated firms operating within countries with lower control of corruption, government effectiveness, political stability, regulatory quality, rule of law, and voice accountability before the EU-ETS implementation.
Keywords: difference-in-differences; distress risk; emission cost; emission permits; environmental score; EU-ETS